UN Peace Operations: Diplomacy, Delivery and New Directions - Wagle, Narayan Prasad (Unity Journal, 2022)
This paper explains roles of diplomacy for better UN (United Nations) Peace Operations, major obstacles in the delivery of mandates of UN Peace Missions, inter alia, due to weaknesses in UN peace architecture and thematic new directions in the course of its evolution. The research methodology involves document analysis and review. The sources of data are UN documents on UN Peace Operations and UN Study reports on the same.It finds the inevitable role of diplomacy in leading discourses, designing and deciding mandates of missions. Due to the political nature of conflicts and dynamic nature of global politics, more effective diplomacy is needed both at global and local level. Reviewing UN peace architecture, it finds that UN Peace Operations are largely successful though beset by some key challenges. Further, it explains such thematic new directions as protection of civilians, women peace and security, concern about safety and security of peacekeepers, regionalism, building and sustaining peace, and growing demand for accountability and professionalism. Finally, some findings and implications for diplomats and peacekeepers involved in UN Peace Operations have been drawn.